Notch-Signaling Deregulation Induces Myeloid-Derived Suppressor Cells in T-Cell Acute Lymphoblastic Leukemia - Grazioli, Paola; Orlando, Andrea; Giordano, Nike; Noce, Claudia; Peruzzi, Giovanna; Abdollahzadeh, Behnaz; Screpanti, Isabella; Campese, Antonio Francesco (Frontiers in Immunology, 2022)
Notch receptors deeply influence T-cell development and differentiation and their dysregulation represents a frequent causative event in ‘T-cell acute lymphoblastic leukemia’ (T-ALL). ‘Myeloid-derived suppressor cells’ (MDSCs), inhibit host immune-responses in tumor environment, favoring cancer progression, as reported in solid- and hematologic-tumors, with the notable exception of T-ALL. Here, we prove that Notch-signaling deregulation in immature T-cells promotes CD11b+Gr-1+ MDSCs in the Notch3-transgenic murine model of T-ALL. Indeed, aberrant T-cells from these mice are able to induce MDSCs in vitro, as well as in immunodeficient hosts. Conversely, anti-Gr1-mediated depletion of MDSCs in T-ALL-bearing mice reduces proliferation and expansion of malignant T-cells. Interestingly, the co-culture with Notch-dependent T-ALL cell lines, sustains the induction of human CD14+HLA-DRlow/neg MDSCs from healthy-donor PBMCs, that is impaired upon exposure to gamma-secretase inhibitors. Notch-independent T-ALL cells do not induce MDSCs, suggesting that Notch signaling acivation is crucial for this process. Finally, in both murine- and human-model, IL-6 mediates MDSC-induction, that is significantly reversed by treatment with neutralizing antibodies. Overall, our results unveil a novel role of Notch-deregulated T cells in modifying T-ALL environment and represent a strong premise for the clinical assessment of MDSCs in T-ALL patients.